Analisis Teknis Implementasi Power Wheeling di Jaringan Interkoneksi Sistem Barito - Yusuf Susilo Wijoyo; Muhamad Rangga Delpiero; Musthafa Abdur Rosyied (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
Power Wheeling is cooperation of using power system network that owned by a party to transmit power from an entity to other entity. Power Wheeling scheme has been implemented in Indonesia since ministry regulation about it has been published. Implementation of Power Wheeling on a system will influence existing system condition. This paper aims to identify the effect of Power Wheeling implementation on a power system in Indonesia, that is Barito System. The result from load flow analysis shows that implementation of power wheeling affectsignificantly on each substation voltage. Short circuit current increases after Power Wheeling implementation but still withinstandard limitation. Stability analysis also shows that system is in normal condition.